Transferring methods to teach business administration from one cultural context to another - Marie Catalo; Nicolas Antheaume; Howayda Ismail (Future Business Journal, 2015)
What happens when a teaching method is transferred from one cultural context to another? In this article we investigate this question by looking at how Computer Based Simulations (CBS) were transposed from a French context to an Egyptian one. In this article we demonstrate, through the case of Egypt, how culture and the characteristics of the school system impact learning abilities. We describe what happens when Egyptian students are confronted with learning modes they have not encountered prior to University, in the context of an Egyptian-French dual-degree programme in business administration and business informatics. We show that the transfer of CBS as a teaching method revealed cultural differences between French and Egyptian students. As a consequence the teaching objectives of CBS were redefined in order to take the Egyptian context into account.
Keywords: 650; Computer-based business simulations; Culture; Egypt; Experiential learning; France; Globalization of Business and Management Education; Learning modes; Management education